(untitled) (CSIAM Transactions on Applied Mathematics, 2023)
We studied linear triblock copolymer and homopolymer mixtures and constructed a new Nakazawa-Ohta-type model to describe the phase separation of the system. For this high-order, nonlocal and multicomponent phase field system, we construct two second-order, linear and energy-stable schemes. We also proved the energy dissipation and mass conservation of the schemes. Finally, numerical simulations were presented in the 3D case, which verified the theoretical analysis. In addition to those reported phase structures, we found some new ones, which can give some guidance to experimenters.